ChemInform Abstract: A Synthesis and Crystal Chemical Study of the Fast Ion Conductor Li7—3xGaxLa3Zr2O12 with x = 0.08 to 0.84. Issue 32 (12th August 2014) - Rettenwander, Daniel; Geiger, Charles A.; Tribus, Martina; Tropper, Peter; Amthauer, Georg
Abstract: The series of garnets Li7.08 Ga0.06 La2.93 Zr2.02 O12, Li6.50 Ga0.15 La2.96 Zr2.05 O12, Li6.48 Ga0.23 La2.93 Zr2.04 O12, Li5.93 Ga0.36 La2.94 Zr2.01 O12, Li5.38 Ga0.53 La2.96 Zr2.00 O12, Li4.82 Ga0.60 La2.96 Zr2.02 O12, and Li4.53 Ga0.72 La2.94 Zr1.98 O12 is synthesized by solid state reaction of stoichiometric mixtures of Li2 CO3, La2 O3, ZrO2, and Ga2 O3 (Pt crucible, 1050 °C, 17 h in air).